DAMPAK MANAJEMEN MODAL KERJA TERHADAP CASH HOLDING PADA INDUSTRI CONSUMER GOODS INDONESIA - Yongki , Yongki; Panjaitan , Risduan; Leon, Farah Margaretha (Catholic University Musi Charitas, 2021)
This study was conducted to examine the impact of working capital management on cash holding in Indonesian consumer goods industries. Cash holding can be managed in various business sectors, such as the industrial sector. This sector investment will bring a future positive impact because it keeps growing continuously by following society's need demands. The manufacturing sector is still the highest source of economic growth in 2018, with 5.17% of the economic growth, 0.91% of it from the manufacturing sector. The samples of this study were consumer goods industry companies that have been go public and listed on the Indonesia Stock Exchange for the 2016-2018 period. There were 34 consumer goods industry companies involved as the samples of this research selected through the purposive sampling technique. Cash holding as the dependent variable was measured using cash and total assets. Working capital net of cash as the independent variable was assessed using current assets, current debt, cash, and total assets. While the cash conversion cycle, financial leverage, company size, sales growth, and cash flow ratios are the control variables. This research used the panel data regression method and individual test (t-test). The results show that working capital net of cash, cash conversion cycle, sales growth, company size, and flow ratio variables have a significant positive effect on cash holding, while financial leverage variable has a significant negative effect on cash holding. For the financial managers of the consumer good industry companies, the implication of this research is the managers need to increase the total number of assets so that the company can fund its business activities, use debt appropriately to increase the efficiency and effectiveness of the company, and increase profits to improve the ability to pay the debt before the due date.